Adhesion Between Rigid Indenter and Soft Rubber Layer: Influence of Roughness - Lyashenko, Iakov A.; Pohrt, Roman (Frontiers in Mechanical Engineering, 2020)
We report a series of experiments on the indentation of steel indenters into a soft layer of transparent rubber with relatively high adhesion. The roughness properties of the steel indenters are varied by undergoing preparation using sandpaper with different grain sizes. Starting from a smooth surface, additional roughness increases the adhesive strength up to a critical roughness value, after which it significantly decreases. Furthermore, we look at the evolution of the contact area during slow indentation and detachment. It is found that during indentation, the contact area changes more sharply compared to detachment (pull-off).